Distinct Midbrain and Habenula Pathways Are Involved in Processing Aversive Events in Humans - Hennigan, Kelly (J Neurosci, 2015)
Emerging evidence implicates the midbrain dopamine system and its interactions with the lateral habenula in processing aversive information and learning to avoid negative outcomes. We examined neural responses to unexpected, aversive events using methods specialized for imaging the midbrain and habenula in humans. Robust activation to aversive relative to neutral events was observed in the habenula and two regions within the ventral midbrain: one located within the ventral tegmental area (VTA) and the other in the substantia nigra (SN). Aversive processing increased functional connectivity between the VTA and the habenula, putamen, and medial prefrontal cortex, whereas the SN exhibited a different pattern of functional connectivity. Our findings provide evidence for a network comprising the VTA and SN, the habenula, and mesocorticolimbic structures that supports processing aversive events in humans.